"Are Your Tanks Filled with Orca Tears?": Crisis Frames and Message Convergence in SeaWorld's Tanked Twitter Campaign. Issue 1 (February 2018) - Woods, Chelsea
Abstract Issues and crises often have multiple frames constructed by organizations and the media. While organizations may try to shape the narrative to their benefit, their ability to do so is often limited. The #AskSeaWorld crisis illustrates this challenge as the online question-and-answer session gone awry generated competing frames from SeaWorld, PETA, and the media. Using a framework of issues management, crisis framing, and message convergence and drawing from organizational documents, media reports, and an interview with PETA, this paper examines the different frames that emerged from the crisis and the extent to which they converged. The findings position SeaWorld as an organization that "protests too much" (Ashforth and Gibbs, Org Sci 1(2):177–194, 1990) and invited a digital crisis by publicly responding to value challenges (Hirsch and Andrews, Leadership and organizational culture, University of Illinois Press, Urbana, 1984). This study also illustrates how a hashtag-based campaign attracts critical publics, such as activists, who can challenge organizational reputations using social media, which may be amplified by media reports. Because many of the media reports reflected content relayed by activists, rather than SeaWorld, this convergence lent legitimacy to activists' claims, heightening SeaWorld's legitimacy challenges.